Iranian Language Teachers and Students Perspectives on Total English Series at Intermediate Level - Azadsarv, Mehdi; Taghvaee, Mohammad; Zangoei, Ali (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
As the means of transferring knowledge between teachers and students, coursebooks play a significant role in educational practices all over the world. Evaluation of coursebooks is also of great significance as it manages to a better understanding of the nature of a specific teaching/learning situation. The present study is an attempt to evaluate Total English coursebook from both Iranian EFL learners and teachers perspectives. Ninety three students and 20 teachers participated in this study. Fifty one of the students and 11 of the teachers were male and 42 of the students and nine of the teachers were female. The range of teachers' experience of teaching the coursebook was between 2-4 years and the range of students' experience of studying the coursebook was between 1-3 years. The data collection took place in three language institutes of Gilan and Mazandaran provinces. The coursebook, evaluated based on modified version of Cunningsworth's (1995) checklist, was the intermediate level of Total English. It was evaluated by both students and teachers based on administering written questionnaires. In order to triangulate the gathered data, 25 percent of the teachers and 10 percent of the students attended an interview session. Data analysis indicated that strength of Total English from teachers' perspective was culture and from students' point of view were visuals as well as practice and testing. Moreover, from students' perspective, the primary shortcoming of the coursebook was phonology.